Air quality assessment in different urban areas from Rio Grande do Sul state, Brazil, using lichen transplants - KOCH,NATÁLIA MOSSMANN (2018)
Abstract Based on the need to monitor air pollution and on the importance of doing it with biological organisms, the present work had as main objective to assess air quality in urban areas through lichen transplants. Besides, we also tested whether there were differences among the studied sites, aiming to point out the main pollution characteristics of the areas. The monitoring was carried out in seven cities, which varied from mainly rural to mainly industrial, in Rio Grande do Sul, southern Brazil. The foliose lichen Parmotrema tinctorum was used as the biomonitor species. Physiological tests and contents of sulphur and heavy metals were measured in the lichen thalli. Other pollutants assessed through air samplers were available for some cities, and modeled concentrations of fine particulate matter and nitrogen oxides for all sites. The effect of air pollution negatively reflected on the physiology parameters of the lichen and the concentration of all heavy metals increased after exposure, especially in the industrial sites. We generated a profile of air pollutants and pointed out that Charqueadas and Esteio had the worst air quality. Since they have high demographic densities, the results are of great public health concern and could be guidelines for future studies.